Gun‐free Zones? Political Opportunities, Resource Mobilization, and Shooting Sports Organizations at U.S. Colleges and Universities. Issue 2 (26th December 2020) - McElroy, Jericho R.; Coley, Jonathan S.
Abstract : Although the general public often thinks of schools as "gun‐free zones, " a growing number of U.S. colleges and universities recognize shooting sports organizations, enabling students to participate in rifle, pistol, shotgun, skeet, and trap sporting events. Building on recent scholarship that employs political opportunity and resource mobilization theories to analyze sports, we assess the roles that states' political characteristics and schools' resources play in the presence of student shooting sports organizations. Drawing on a comprehensive database of 1, 953 four‐year colleges and universities in the United States, and employing logistic regression analyses, we show that Republican‐leaning states, schools with larger, mostly white, and majority men student bodies, and schools with Republican student organizations serve as conducive environments for shooting sports organizations. This article represents the most comprehensive study to date of shooting sports in U.S. schools and contributes to literatures on the sociology of guns, the sociology of sports, and social movements.